Quantum Listening - Oliveros, Pauline 1932-2016; Anderson, Laurie -1947; Ione, Carole -1937; Satz, Aura -1974 (United Kingdom Ignota, 2022)
What is the difference between hearing and listening? Does sound have consciousness? Can you imagine listening beyond the edge of your own imagination? In response to the anti-war movements of the 1960s, pioneering musician and composer Pauline Oliveros began to expand the way she made music, experimenting with meditation, movement and activism in her compositions. Fascinated by the role that sound and consciousness play in our daily lives, Oliveros developed a series of Sonic Meditations that would eventually lead to the creation of Deep Listening – a practice for healing and transformation open to all, rooted in her musicianship. Quantum Listening is a manifesto for listening as activism. Through simple yet profound exercises, Oliveros shows how Deep Listening is the foundation for a radically transformed social matrix: one in which compassion and peace form the basis for our actions in the world. This timely edition brings Oliveros’ futuristic vision – blending technology and spirituality – together with a new Foreword and Introduction by Laurie Anderson and IONE.
Keywords: Music philosophy and esthetics; Listening